PERLINDUNGAN HUKUM KONSUMEN TERHADAP BARANG YANG TIDAK LAYAK EDAR - Anggraeni Endah Kusumaningrum (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Globalization and free trade deal to expand the flow of goods and services so that the goods or services offered vary in the production of foreign and domestic. It is useful to consumers because their needs are meeting. Above all, the circumstances but the position of businesses and consumers become unbalanced because business use it to search for maximum profit, consumers in a weak position because of consumer awareness of their rights remains low. Consumer awareness on their rights and obligations necessary to avoid the consumption of goods that is not feasible. A product can be a viable product must meet minimum standards. Consumers will be protected from product that are not worth consume. Therefore, consumers should take an active role. That is why being smart consumers are very essential.